Strategi dan ciri kesantunan berbahasa Jepun (Jurnal Bahasa, 2006)
This study is a pragmatic study which focuses on linguistic politeness and conversational styles of Japanese nature speakers in verbal inter-actions. The Japanese speakers in this study comprise the teaching staff from Japan in Ambang Asuhan Jepun (AAJ), Pusat Asasi Sains, Uni-versity Malaya. The data for this study is collected from recordings, field notes and observations taken during staff meeting. The perspec-tives adopted in this study are based on the studies of relevant linguistic scholars such as Leech and the works of Osamu Mizutani The study focuses on linguistic politeness of Japanese language, showing their politeness when interacting among the speakers. The methodology used in this study is the qualitative method based on Leech. The result of this study indicates that the Japanese speakers are cooperative and practice politeness strategies throughout their interaction.